Assessment of Records Management Practices at Uganda College of Commerce Kabale. - Tukamushaba, Olivia (Kabale University, 2024)
The research examined the state of records management practices at Uganda College of Commerce Kabale. Its objectives were to assess current practices, identify associated challenges, and propose solutions. Using a descriptive research design, data was gathered through interviews and observations. Findings revealed various aspects of records management practices, including creation, storage, access control, retention, monitoring, and disposal procedures. Challenges identified encompassed record inaccessibility, system insecurity, technical complexities, information proliferation, and the dilemma of determining what to retain or discard. Proposed solutions included ensuring retention and durability, providing secure storage, offering continuous training programs, acknowledging the diversity of paper and electronic records, maintaining authenticity, proper disposal, and utilizing computer-based management practices. Recommendations emphasized the necessity of training registry staff on effective records management and digital systems usage, highlighting the importance of accessible records and ongoing support. Additionally, implementing access controls in digital systems to safeguard sensitive information while facilitating authorized access, and regularly updating controls to align with evolving roles and responsibilities were advised.